THE USE OF INFORMATION TECHNOLOGIES IN PEDAGOGICAL ACTIVITIES (Ustozlar uchun, 2026)
This study investigates the integration of information and communication technologies (ICT) in pedagogical activities at secondary and preschool education levels. Drawing on a mixed-methods approach encompassing a survey of 420 educators across Uzbekistan and an analysis of global best practices, the research reveals significant correlations between ICT adoption and improved student engagement, academic performance, and 21st-century skill development. The study identifies key barriers — including insufficient infrastructure, limited teacher training, and lack of localized content — and proposes evidence-based recommendations. The findings affirm that systematic ICT integration, supported by institutional policy and professional development, holds transformative potential for modern Uzbek pedagogy.